THE ROLE OF PERCEIVED VALUE IN MEDIATING THE EFFECT OF PACKAGING DESIGN AND BRAND IMAGE ON PURCHASE INTENTION OF PENTOLAN - Nicholas Alexander; Michael Ricky Sondak (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The transformation of the culinary industry requires MSMEs, particularly in the street food sector, to adapt visually and strategically to modern consumer behaviour. This study aims to analyse the role of perceived value in mediating the effect of packaging design and brand image on the purchase intention of "PENTOLAN" products. The data were collected from 240 respondents and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to evaluate both the measurement and structural models. The findings demonstrate that packaging design and brand image have a positive and significant effect on perceived value. Interestingly, neither packaging design nor brand image directly and significantly influences purchase intention. Instead, perceived value acts as a full mediator, predominantly and significantly driving consumer purchase intention. Visual appeal and brand popularity will not directly trigger a transaction unless accompanied by an adequate assessment of value. These findings provide practical implications for culinary MSMEs seeking to design a holistic marketing strategy, in which aesthetic updates must be balanced with the rationality of price, portion, and taste quality.